2022
DOI: 10.1155/2022/3838222
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic Approach in Ambulatory Vitrectomy: Peribulbar Block vs. Balanced General Anesthesia

Abstract: Background. Vitrectomy is one of the most common outpatient ophthalmic surgeries. The anesthetic technique used in outpatient surgery should contribute to a faster functional recovery, better pain control, and fewer complications. The aim of this study was to compare peribulbar block and balanced general anesthesia, in patients undergoing outpatient vitrectomy. Methods. A prospective cohort study was carried out, including adult patients undergoing ambulatory vitrectomy, between January and February 2018. Peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Compared with general anesthesia, regional anesthesia with MAC provides faster functional recovery, better pain control, and fewer complications, such as intraoperative hypotension. 24 However, studies have shown that two-thirds of patients heard the surgeons talking and that one-third of patients reported objects moving during PPV with MAC. 25 In terms of analgesic eye relaxation and the surgical eye position, the satisfaction of patients and surgeons with regional anesthesia was only one-fourth that with general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with general anesthesia, regional anesthesia with MAC provides faster functional recovery, better pain control, and fewer complications, such as intraoperative hypotension. 24 However, studies have shown that two-thirds of patients heard the surgeons talking and that one-third of patients reported objects moving during PPV with MAC. 25 In terms of analgesic eye relaxation and the surgical eye position, the satisfaction of patients and surgeons with regional anesthesia was only one-fourth that with general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…The peribulbar block technique is useful for patients willing to stay for a short time in the hospital. It has many advantages including a low incidence of cough and emesis during the immediate postoperative period (4) .…”
Section: Introductionmentioning
confidence: 99%